Qualified to care? A comparative study on the experiences of formal and informal caregivers of individuals with disabilities - Liao, Qianyu (2018)
This comparative study examined the experiences of formal and informal caregivers of individuals with disabilities in Singapore. From a role theory perspective, caregiving experiences are analysed through their: 1) challenges and their coping strategies; 2) motivation of caregiving; and 3) support received. With rising populations of individuals diagnosed with disabilities and the trend of externalising care provision, this study addresses variables affecting caregivers’ role strains to enhance their experiences. Through semi-structured interviews with 23 respondents who described their daily care routines, findings revealed that both groups of caregivers were motivated to provide care out of affection and the social support they received from families and friends. However, the experiences of role strains, types of coping strategies and access to support were fundamentally different. Therefore, a differentiated approach to providing caregiver support would benefit formal and informal caregivers in reducing their role strains, enhancing the overall quality of care in Singapore.